2009
DOI: 10.1186/1472-6750-9-71
|View full text |Cite
|
Sign up to set email alerts
|

Archaeosomes made of Halorubrum tebenquichensetotal polar lipids: a new source of adjuvancy

Abstract: Background: Archaeosomes (ARC), vesicles prepared from total polar lipids (TPL) extracted from selected genera and species from the Archaea domain, elicit both antibody and cell-mediated immunity to the entrapped antigen, as well as efficient cross priming of exogenous antigens, evoking a profound memory response. Screening for unexplored Archaea genus as new sources of adjuvancy, here we report the presence of two new Halorubrum tebenquichense strains isolated from grey crystals (GC) and black mood (BM) strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 62 publications
3
24
0
Order By: Relevance
“…These reports are in accordance with our records. Gonzalez et al [17] reported same results for ARC. The cytotoxicity effect of the archaeosomal paclitaxel formulation probed by MTT assay and as a result the archaeosomal formulation without any drug indicated a negligible cytotoxicity effect on MCF-7.…”
Section: Discussionsupporting
confidence: 74%
“…These reports are in accordance with our records. Gonzalez et al [17] reported same results for ARC. The cytotoxicity effect of the archaeosomal paclitaxel formulation probed by MTT assay and as a result the archaeosomal formulation without any drug indicated a negligible cytotoxicity effect on MCF-7.…”
Section: Discussionsupporting
confidence: 74%
“…Immunization of mice with ovalbumin (OVA) entrapped in all archaeosomes lipid compositions evoked a primary (day 10) splenic CTL response indicating processing for MHC class I presentation. Polar lipid compositions from halophilic archaea were very potent to adjuvant this early CTL response (Gonzalez et al, 2009). The lytic units reduced significantly by weeks 6-7.…”
Section: Applications Of Archaeosome Formulationsmentioning
confidence: 95%
“…Therefore, in this work, a commercial hydrophobic ZnPc was loaded into TPAs containing liposomes, and its in vitro leishmanicidal activity was compared to that of ZnPc loaded in UDLs on macrophages infected with L. braziliensis amastigotes. 37 Cultures were monitored by absorbance at 660 nm and harvested in the late stationary phase for storage as frozen cell pastes.…”
Section: Introductionmentioning
confidence: 99%